STATUS OF EXPLOITATION OF MARINE RESOURCES IN THE WORLD BIOSPHERE RESERVE OF CU LAO CHAM - HOI AN - Long, Nguyen Van; Dat, Mai Xuan (Vietnam Journal of Marine Science and Technology, 2019)
Assessments of commercial and seed resources of target species in the waters of the World Biosphere Reserve of Cu Lao Cham - Hoi An were conducted through 11 consultations at 11 local communes/wards surrounding the Reserve in November-December 2015 in combination with analysis of 150 samples collected from fishing boats using various fishing gears and landing sites in the rainy (November 2015) and dry (June 2016) seasons. Assessments of spawning and nursery grounds of target resources were conducted in three main periods (December 2015, June and August 2016). Results from this study show that there were 29 fishing gears catching more than 208 species of fishes, molluscs, crustaceans, echinoderms and polychaetes, in which 36 species are considered as target resources. The total catch of commercial and seed resources was about 12,796.4 tons and 7,405,800 individuals (7,020,400 seeds equivalent to 780 kg of seeds of orange-spotted spinefoot and 385,400 seeds of mangrove red snapper, orange-spotted grouper, malabar grouper, spotted scat and mud crab), giving a revenue of 210 billion VND (about 9.5 million USD) harvested in 2015, in which fishes are the most important resources. The waters surrounding the coral reefs and estuary supported a total catch of about 10.8 and 22.2 times higher than that in the Thu Bon estuary and the coral reefs in Cu Lao Cham islands respectively. The area surrounding the mud flats (Go Hi) in Cam Thanh commune where nypa palms and seagrasses grew is the most important nursery ground for seeds of target species.